Laser photoresection in the preoperative assessment of a bronchial adenoma. Issue 9 (September 1988) - Stanley, P R; Anderson, T; Pagliero, K M
Abstract : Preoperative laser photoresection of a bronchial adenoma allowed more accurate evaluation and better planning of the operative procedure.